2014
DOI: 10.1111/1754-9485.12170
|View full text |Cite
|
Sign up to set email alerts
|

The location of origin of spontaneous extracranial internal carotid artery dissection is adjacent to the skull base

Abstract: CAD occurring spontaneously or due to indirect trauma most frequently involves the distal extracranial ICA. Spontaneous CAD is associated with vessel redundancy, and the risk of acute stroke is greatest with occlusive CAD. The prognosis is good with treatment, with a low rate of recurrent stroke and a high rate of vessel remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…This may be due to wall stress increases in the intima in this region due to head movements [5,6]. However, in 1 case series, 49.0% of carotid dissections were only in the distal third of the internal carotid artery, 96.1% involved the distal two-thirds, with only 3.9% originating in the proximal one-third [7]. In another study, based on computed tomography, MR or digital subtraction angiography, dissection at segment III (corresponding with the first and second cervical vertebrae) was the most common site (37.5%) of carotid artery dissection during trauma, while in spontaneous dissection, segment I (origin of the vessel to the fifth cervical vertebrae) was the most common site (55%) [8].…”
Section: Discussionmentioning
confidence: 93%
“…This may be due to wall stress increases in the intima in this region due to head movements [5,6]. However, in 1 case series, 49.0% of carotid dissections were only in the distal third of the internal carotid artery, 96.1% involved the distal two-thirds, with only 3.9% originating in the proximal one-third [7]. In another study, based on computed tomography, MR or digital subtraction angiography, dissection at segment III (corresponding with the first and second cervical vertebrae) was the most common site (37.5%) of carotid artery dissection during trauma, while in spontaneous dissection, segment I (origin of the vessel to the fifth cervical vertebrae) was the most common site (55%) [8].…”
Section: Discussionmentioning
confidence: 93%
“…10) Dissection has also been reported to occasionally start 20–30 mm distal to the carotid bifurcation. 11,12) We need to keep this distance in mind when manipulating the microguidewire.…”
Section: Discussionmentioning
confidence: 99%
“…Wall stress of the intimal side of the ICA increased at the skull base and the cranial edge of the carotid sinus. Downer et al 5 reported that 36 (94.7%) of 38 vessels had maximum mural hematoma thickness in the distal third of the ICA and that fixation of the ICA at the cranial base was related to the pathology of ICA dissection. In the present case, the left ICA was fixed at the skull base and at the ICA portion compressed by the osteophyte and was highly stretched between these two portions during neck rotation.…”
Section: Discussionmentioning
confidence: 99%